Central limit theorem for random "contractive" functions on interval - Block, Maciej; Kacprzak, Wiktoria; Falęcki, Dorian (Annales Mathematicae Silesianae, 2025)
We use the approach from Czudek and Szarek (see [1]) to prove the central limit theorem for a stationary Markov chain generated by an iterative function system for a family of increasing, injective functions on [0, 1] with "contractive" properties. We introduce a new approach to prove existence of an unique invariant measure using e-property (see [2]).